Development and validation of an improved atomization model for GDI spray simulations: Coupling effects of nozzle-generated turbulence and aerodynamic force. (1st September 2021) - Li, Yaoting; Huang, Yongcheng; Luo, Kun; Liang, Mengmeng; Lei, Bin
Highlights: An improved atomization model for GDI spray simulations is developed and validated. Turbulent and aerodynamic effects are both considered on primary breakup modeling. Spray morphology, spray tip penetration and SMD are well predicted simultaneously. ρ f / ρ g shows a great impact on the sensitivity of the proposed atomization model. Abstract: By coupling the Wu-Faeth (WF) turbulent primary breakup theory with the classical Kelvin-Helmholtz (KH) and Rayleigh-Taylor (RT) aerodynamic instability theories, the influences of nozzle-generated turbulence and aerodynamic force on the GDI spray atomization were both modeled in this study. The developed WF-KH-RT model was applied to the spray simulation of a six-hole GDI injector. The model calibration showed that with a simple tuning of a few model parameters, the WF-KH-RT model could predict the spray morphology, spray tip penetration (STP) and Sauter Mean Diameter (SMD) under various injection pressure and ambient pressure conditions with a high fidelity. The influences of specific WF-KH-RT model parameters on the spray simulation were also studied. The results revealed that increasing the KH characteristic time constant B 1, WF characteristic length constant C sx and RT characteristic length constant C RT will lead to the increase of STP and SMD under most conditions. As the ratio of fuel density to ambient density ρ f / ρ g decreases, the aerodynamic effect is enhanced while the turbulent effect is weakened in the primary breakup, as a result the sensitivity of STP and SMD to B 1 increases, while that to C sx declines. In summary, the results of this study can provide an insight into the relationship between different mechanisms affecting the fuel spray atomization, and an instruction of calibrating the proposed novel atomization model in GDI engine spray simulations.